Searching for meaning and purpose in elite sport: A narrative review of sport psychology literature with theoretical insights from psychology - Oblinger-Peters, V.; Henriksen, K.; Ronkainen, N. J. (Psychology of Sport and Exercise, 2025)
Athletes` stories about their experiences in elite sport inevitably evoke the notion of meaning, a concept, which has appeared in many shapes and forms within sport psychology. Qualitative scholarship, for example, has generated a large literature base on the meaning of experience (i.e., implicit meaning) in elite sport. However, the experience of meaning(fulness) (i.e., existential meaning) has received less scholarly attention and has rarely been the explicit study object. To assist theorizing and the empirical investigation of meaning and purpose in elite sport in these early stages, we take stock of the emerging body of literature in sport psychology. The article has three parts: Firstly, we distinguish between implicit and existential meaning to delineate our study object. Secondly, we introduce psychological theory to show how existential meaning can be conceptualized (e.g., dimensions, sources, crisis of meaning). Thirdly, we analyzed 23 studies in a narrative review approach to understand how meaning (n = 17) and purpose (n = 6) in elite sport have been understood, and what we know about these concepts empirically. The current scholarship revealed itself heterogenous in terms of study designs, methodologies, theoretical frameworks, and conceptualizations of meaning and purpose. Findings are discussed in eight overarching themes (e.g., moments when meaning and purpose are questioned; as mechanism and indicator of growth following adversity) to map the reviewed literature comprehensibly and to provide a foundation for applied work. The article concludes by highlighting unresolved issues and proposing future directions for studying and applying existential meaning in elite sport.